How COVID-19 highlighted the need for infection prevention and control measures to become central to the global conversation: experience from the conflict settings of the Middle East. (October 2021) - Mouallem, Roula El; Moussally, Krystel; Williams, Anita; Repetto, Ernestina; Menassa, Marilyne; Martino, Chiara; Sittah, Ghassan Abu
Abstract: Within just a few months, the coronavirus disease 2019 (COVID-19) pandemic managed to bring to the foreground the conversation that infection prevention and control (IPC) experts have been pushing for decades regarding the control of the spread of infections. Implementing the basics of IPC has been a challenge for all affected countries battling with an exponential COVID-19 curve of infection. Preventing nosocomial transmission of the disease has been difficult in highly resourced and stable contexts, but even more so in the conflict context of the Middle East. COVID-19 has added further challenges to the long list of existing ones, hindering the implementation of the optimal IPC measures that are necessary to break the chain of infection of both respiratory and non-respiratory infections in those settings. This paper outlines and gives examples of the challenges faced across the Middle East conflict setting and serves as a call for action for IPC to be prioritized, given the resources needed, and fed with contextualized evidence.